Penerapan Konseling Kelompok Solutions-Focused Brief Therapy untuk Menurunkan Stres Akademik Siswa - Della Genita Permata Hati Wahyudi; Isfauzi Hadi Nugroho; Lely Yuanita (CV. ITTC INDONESIA, 2025)
This study aims to determine the effectiveness of Solution-Focused Brief Group Counseling in reducing academic stress among high school students. The study uses a classroom action research method combined with a quantitative experimental approach using a one-group pretest and posttest design. The target population of this study consists of 38 tenth-grade students from class 10 J at SMAN 1 Kediri. The subjects were selected through purposive sampling, with 4 students chosen based on the highest academic stress scores. The Solution-Focused Brief Group Counseling was conducted in two cycles, with each session lasting 40 minutes. The development of the academic stress scale instrument was based on Robotham’s theory of academic stress (2008). Based on the results of the pretest, treatment in cycles 1 and 2, posttest, and Wilcoxon analysis, it can be concluded that Solution-Focused Brief Group Therapy is effective in reducing academic stress.